The question under consideration is the ways of determining the physical working capacity of juvenile sportsmen in the conditions of sport training (on the example of running test) on the basis of conducting single submaximal loading - Khoroshukha M.F (Kharkov National Pedagogical University, 2010)
The comparative analysis of physical capacity of young sportsmen is resulted 13-16 years. 30 teenagers took part in an inspection. Between two methods of determination of physical capacity of the trained and untrained teenagers by the specific loadings there are not statistically possible differences. Determination of PWC170(V) in at run with the use of only one submaximl loading not accompanied the possible origin of subzero reactions from the side of inspected. Such approach can be used in practice of sport, sporting medicine and health mass sport.